Essentials of craniomaxillofacial trauma (Quality Medical Publishing, 2012)
Essentials of Craniomaxillofacial Trauma is destined to become a favorite with all students of plastic surgery, otolaryngology, and maxillofacial surgery, whether residents in training or experienced practitioners. Small enough to fit in a lab coat pocket but comprehensive enough to cover the essential topics in facial trauma, this exceptional manual is just the resource you need. It will prove invaluable as a quick reference on the "front lines" in the emergency room as well as for use in daily practice, when studying for board exams, or simply as a refresher when confronting a difficult clinical problem.